Investigation of the Arrhythmia Parameters of Hemodialysis Patients with Hypotensive Episodes - Yalım, Zafer; Demir, Mehmet Emin; Alp, Çağlar; Özkan, Melike; Yalım, Sümeyra Alan (International Journal of Innovative Research in Medical Science, 2019)
Background: Sudden cardiac death is the leading cause of cardiac caused death in hemodialysis patients. Hypotensive episodes in pre- intra and post-dialytic periods are the serious clinical challenges that effect patients life quality and prognosis. We investigated whether hypotensive episodes have an association with ventricular arrhythmias and discuss literature. Methods: Totally 56 cases; twenty-two patients with frequent hypotension episodes, and 15 normotensives patients who were on maintenance hemodialysis treatment and 19 healthy individuals were included in the study. Pre-intra and post-dialytic periods recorded by using a 24-h Holter rhytm device. p< 0,05 is postulated as significantly distinct. Results: Records of 50 participants were evalated properly. Both in hypotensive and normotensive hemodialysis patients ventricular extrasystoles [VES] counts were in a strong relation with lower blood pressure p<0,05. Comorbid diseases [diabetes mellitus, coronar artery disease] which may lead arrhtymias were similar in all three groups. 16 of 18 hyptensive patients also were non-dipper [p<0,05]. Conclusion: Our study revealed that frequent hypotensive episodes are associated with arrhythmia. Clinicians should be aware of arhhythmia which is most important cause of sudden cardiac death and must consider performing a deep cardiological evaluation.